(untitled) (Journal of the College of Basic Education, 2022)
The present study included identification the active compounds of an Macro-algae from the Iraqi water ecosystem . The macro-algae , Cladophora glomerata & Chara vulgaris which isolated from water cannel in Baghdad University during April 2016. Physic-chemical parameters were measured , such as air and water temperature, pH , Ca+2 , Mg+2 , Cl- , No2- , No3- , Po4- and So4- . Results indicated that the active chemical compounds in the hot methanolic and ethanolic extracts for Cladophora glomerata & Chara vulgaris were Alkaloid, Tannins, Saponins , Resins , Terpenes, phenols and Flavonoids .These findings suggest the possibility of using the Cladophora glomerata & Chara vulgaris as a novel source of natural antimicrobial agents in pharmaceutical industries.